2012
DOI: 10.1371/journal.pone.0040356
|View full text |Cite
|
Sign up to set email alerts
|

Helminth Antigens Enable CpG-Activated Dendritic Cells to Inhibit the Symptoms of Collagen-induced Arthritis through Foxp3+ Regulatory T Cells

Abstract: Dendritic cells (DC) have the potential to control the outcome of autoimmunity by modulating the immune response. In this study, we tested the ability of Fasciola hepatica total extract (TE) to induce tolerogenic properties in CpG-ODN (CpG) maturated DC, to then evaluate the therapeutic potential of these cells to diminish the inflammatory response in collagen induced arthritis (CIA). DBA/1J mice were injected with TE plus CpG treated DC (T/C-DC) pulsed with bovine collagen II (CII) betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 43 publications
2
49
1
Order By: Relevance
“…Indeed, protection induced by infection with the live parasite was found to be TGF-b dependent. It has also been reported that somatic extracts from F. hepatica enhance Treg differentiation (20). In this study, we found that FHES induced dose-dependent production of TGF-b by GM-CSF-expanded BMDCs ( Fig.…”
Section: Role Of Regulatory Cytokines and Cells In The Immunosuppresssupporting
confidence: 75%
See 1 more Smart Citation
“…Indeed, protection induced by infection with the live parasite was found to be TGF-b dependent. It has also been reported that somatic extracts from F. hepatica enhance Treg differentiation (20). In this study, we found that FHES induced dose-dependent production of TGF-b by GM-CSF-expanded BMDCs ( Fig.…”
Section: Role Of Regulatory Cytokines and Cells In The Immunosuppresssupporting
confidence: 75%
“…The live fluke probably exerts distinct immunomodulatory effects to FHES, because of the additional effect of tegumental and somatic Ags. Total extract of F. hepatica, a soluble preparation of homogenized adult flukes that contains tegumental and somatic Ags, was shown to protect mice from collagen-induced arthritis in a TGF-b and Treg-dependent manner (20). In contrast, the current study demonstrates that ES fraction suppresses not by Tregs but by modulation of innate immune responses, specifically the induction of IL-5 and IL-33.…”
Section: Discussioncontrasting
confidence: 55%
“…Tregs induce protection against CIA by diminishing joint inflammation (Carranza et al, 2012). Therefore, we evaluated the levels of Tregs in LNs isolated from CIA mice at day 40 and found that IQ-1S (20 and 30 mg/kg) treatment dose-dependently increased the number of CD4 1 cells expressing CD25 and Foxp3 (Fig.…”
Section: Inhibition Of Collagen-induced Arthritis By Iq-1smentioning
confidence: 94%
“…Adoptive transfer of bone marrow-derived DCs pulsed with Fasciola hepatica (i.e. trematode parasite) tegument antigens and the TLR9 agonist CpG-DNA resulted in reduced severity of collagen-induced arthritis in mice that was dependent on Treg cells; F. hepatica antigen only treated DCs did not suppress arthritis [16]. Also, DCs pulsed with T. spiralis antigen protected mice from experimental autoimmune encephalitis (a model of multiple sclerosis) and while this correlated with DC production of IL-10, the mechanism(s) of action by these cells was not defined [39].…”
mentioning
confidence: 99%